O Chile contemporâneo na historiografia política de Tomás Moulian - Martins, Camila Savegnago [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This dissertation intents to discuss the contribution of the Chilean intellectual and social scientist – Tomás Moulian, on the building of the political historiography of contemporary Chile, using its main works and studies about the country. Therefore, it is fundamental the understanding of the politic-cultural formation of the Latin-American intellectual, as well as other elements that constitutes it: sociability networks, exile, political acting, among others. Not less important is the investigation of thoughts influences received by Moulian over his trajectory. It’s a reflection on how important political processes, that occurred on the second half of the 20th century in Chile, as the ascension and overthrow of Salvador Allende and the Popular Unity of the power (1970-1973), the military government of Augusto Pinochet (1973-1989), the transition to democracy and even the after-concertación, are seen, related and interpreted by the author. From this thorough analysis, considering also different actors that compound and still are part of the political spectrum of Chile, it’s going to be possible to establish a dialog with one of the keys of interpretation of the author, called “transformismo”, that, according to Moulian, constitutes one of the important elements in comprehending contemporary Chile’s transformation. Hence, the aim of the research is also to approach new elements existents on the intellectual Tomás Moulian approaches perspectives: questions involving the conception of a new socialism to Chile on the 21th century, the deepening of democracy and the diverse elements that constitutes it, that also are part of contemporary Chile

A presente dissertação analisa e discute a contribuição de um intelectual e cientista social chileno– Tomás Moulian - sobre a construção da historiografia política do Chile Contemporâneo, mobilizando suas principais obras e estudos sobre o país. Para tanto, é fundamental o entendimento da formação político-cultural do intelectual latino-americano, bem como de elementos que o constituem: redes de sociabilidade, exílio, atuação política, entre outros. Não menos importante é a investigação das influências de pensamento recebidas por Moulian ao longo de sua trajetória. Trata-se de refletir como importantes processos políticos, ocorridos na segunda metade do século XX no país, tais como a ascensão e a derrubada de Salvador Allende e a Unidade Popular do poder (1970-1973), o governo militar de Augusto Pinochet (1973-1989), a transição para a democracia e até mesmo o pós-concertación, são vistos, relacionados e interpretados pelo autor. A partir dessa minuciosa análise, considerando também diferentes atores que compunham e ainda fazem parte do espectro político do Chile, será possível estabelecer um diálogo com uma das chaves de interpretação do autor, denominada transformismo e que, segundo Moulian, constitui um dos elementos importantes para a compreensão da transformação do Chile contemporâneo. Sendo assim, por fim, o intuito da pesquisa é também o de abordar novos elementos presentes nas convicções e perspectivas de abordagem do intelectual Tomás Moulian: questões que envolvem a concepção de um novo socialismo para o Chile no século XXI, o aprofundamento da democracia e os diversos elementos que a constituem, que também fazem parte do Chile Contemporâneo
Keywords: História; História política - Chile; Historiografia; Intelectuais e política; Chile - Política e governo; History